(3TQM bGfhf GdYbhHGJ (B:s (3GdLQGFe GdhGbYI Ydi GdCehGd (B= Explanation of the penal code : crimes against fund /s - (3GdSYjO, cGeds ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2014)
(3jJfGhd gPG GdcJGH GdLQGFe GdhGbYI Ydi GdTQa, cGdPe Ch GdeOM Gdh LGgj Ch GdZjGHj Ch GddMXj eY GdYdfjI aGdfU GdbGfhfj ddPe YfO GdeTQY GdCQOfj gh ESfGO eGOI eYjfI Edi TNU eG hdh aj eYQV GdTc hGdGSJagGe ef TCfgG Cf JfGd ef TQa hcQGeJg Ch JYQVg Edi HZV GdfGS hGMJbGQge ShGA CcGfJ Jdc GdeGOI LQjeI JSJdRe GdYbGH Ce dG hjfJbd Edi YbhHI GdPe MOO GdTGQY YbhHJg HGdMHS ef TgQjf Edi SfI hjecf EQLGY GdXQha GdeTOOI Edi UaI GdeLfj Ydjg hjbhe HgPg GdUaI XQaGf jaJQV Cf GdeLfj Ydjg eLdS GdCeI Ch CMO CYVGFg CKfGA Yedg Ch EMOi GdgjFGJ GdQSejI Ch GdeMGce hGdEOGQI GdYGeI Ch GdLjT Ch LdGdI Gdedc Ch ef gh aj Mce hYdI GdJTOO aj Cf GdPe GdehLg Edi GdaFGJ GdePchQI dG jUjHge HUaJge CaQGO YGOjjf aj GdeLJeY hEfeG HUaJge ef YeGd GdOhdI heeKdjge dgG hJJWdH GdeUdMI GdYGeI Cf JbOe GdMeGjI dge Ydi fMh Cbhi eeG JbOe ddehGWfjf GdYGOjjf hjTjQ aj GdaUd GdKGfj Edi GdbOM hgh GdGYJOGA Ydi cQGeI GdZjQ hTQaI Ch GYJHGQ hdh aj eYQV GdTc hGdGSJagGe Ohf HjGf eeJOI eYjfI hEPG cGf GdeTQY bO Ch ef gh aj Mceg EdG Cf TOO GdYbGH CjVG Ydi ef jbOM ehXaG TOO GdYbGH Ydi ef jPe ehXaG habG CeG aYdg GdeTQY GdeUQj HGdfSH ddSH hGdJMbjQ (B((3gh cd CSHGH Ch JMbjQ ZjQ GdPe Ch GdbOM jhLg Edi GdeYJOi Ydjg hLgG dhLg HGdcdGe Ch GdMQcGJ Ch HcJGHI hGdQSe hYdGbI gPg GdLQGFe GdKdGK JJeKd HYVgG HHYV(B)(3, hgcPG aEf gPg GdOQGSI Jbhe Ydi GdCHhGH GdJGdjI(B: (3GdHGH GdChd NUUfGg dOQGSI GdLQGFe GdhGbYI Ydi GdYQV, GdHGH GdKGfj NUUfGg dLQGFe GdMV Ydi GdaLhQ hGdJYQV ddCNdGb hGdBOGH GdYGeI, GdHGH GdKGdK NUUfGg dLQGFe GdELgGV, GdHGH GdQGHY NUUfGg ddLQGFe GdhGbYI Ydi GdCSQI(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3bGfhf GdYbhHGJs -- (3GdCQOfs; (3LQGFe GdCehGds -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs